Advanced classification techniques for healthcare analysis - Chakraborty, Chinmay 1984- (IGI Global, Disseminator of Knowledge, 2019)
"This book focuses on classification techniques which broadly deals in delivery of quality, accurate and affordable healthcare. It also examines the potential for making faster advances in many scientific disciplines and improving the profitability and success of different enterprises"...Provided by publisher
Includes bibliographical references
Keywords: Image Interpretation, Computer-Assisted; Classification; Image Processing, Computer-Assisted